Evaluation of hormonal change, biochemical parameters, and histopathological status of uterus in rats exposed to 50-Hz electromagnetic field - Aydin, M.; Cevik, A.; Kandemir, F. M.; Yuksel, M.; Apaydin, A. M. (Sage Publications Inc, 2009)
This study investigates the effects of the electromagnetic field (EMF) resulting from the 170 kV high-voltage power lines on hormonal status, on progesterone and 17-beta estradiol levels, and on morphology of the uterus and ovaries associated with biochemical parameters of adult Wistar female rats. The rats were assigned to experimental (21) and control groups (7). The rats in the experimental group were housed in a wooden barn with 7.5 m in vertical distance to the power line. Groups 1, 2, and 3 were exposed continuously (24 h) to electric-electromagnetic fields (ELF-EMFs) (48.21 +/- 1.58 mG) for 1, 2, and 3 months, respectively. The rats of group 4 served as the control and were placed in laboratory conditions (The average value of the ELF was 0.75 +/- 0.05 V/m. The value of the EMF was calculated to be 0.48 +/- 0.05 mG.). Significant (P < 0.05) decreases were determined among the groups in terms of reproductive organ weights (uterus and ovaries) and progesterone and estrogen levels in relation to the varying periods of the estrous cycle. Although marked reductions (P < 0.05) were observed among the groups in relation to plasma catalase activity, depending on exposure time, no significant differences were found in terms of glutathione and malondialdehyde levels. It is concluded that exposure to the ELF-EMFs for different time periods produced significant decreases in plasma catalase activities in the 3-month exposure groups but no effects on progesterone level, on 17-beta estradiol level, or on the morphology and weight: of uterus and ovaries. Toxicology and Industrial Health 2009; 25: 153-158.
Keywords: electromagnetic fields; female rat; histopathological events; hormonal status